Folklore Songs as Means of Raising Awareness or Enforcing Nationalist Differences: Arab Idol as a Case Study - Jarrar, Yosra; Awobamise, Ayodeji; Bukhari, Shema (Dirasat: Human and Social Sciences, 2019)
This study critically explores whether folklore songs performed in Arab Idol enforce nationalist differences or tend to raise awareness of current political and social issues. Using an inductive framing approach, the audience’s comments on four Arab Idol videos of four contestants performing folklore patriotic hymns are analyzed, described and categorized according to Thompson’s (1990) five semantic process through which ideology is articulated. Findings show that folklore and patriotic hymns performed by contestant in Arab Idol amplify nationalist differences more than they tend to raise awareness among Arabs.